Terapi Aktivitas Kelompok (TAK) Pada Lansia Dengan Demensia di Panti Sosial Tresna Werdha Budi Mulia 1 Cipayung - Samsuni, Samsuni; Susanti, Fajar; Ginting, A.G. Nopres; Herlatini, Ayu Dewi; Yuniarti, Endah; Febriana, Wilda; Polpa, Eksel (Universitas Respati Indonesia, 2024)
AbstractAn elderly person is someone who has reached the age of 60 years and over, both men and women, who is still able to carry out work or activities that can produce goods and services or is unable to earn a living so his life depends on other people. Group activity therapy is a type of therapeutic modality that can be created by nurses in a group of elderly people to improve cognitive function in the elderly. Three times in 3 weeks, namely coloring therapy, guessing spiritual pictures and guessing general pictures, is one of the group activity therapy options for the elderly which improves cognitive function. The aim of implementing this group activity therapy activity is to improve cognitive function in the elderly at the Thesna Werdha Budi Mulia 1 Cipayung Social Home. The participants in this activity were 6 elderly people at Wisma Dahlia. The methods used in this activity were lectures, demonstrations and discussions. The results of the activity showed that the elderly were actively and enthusiastically involved in this activity and were able to color and guess its function correctly. It can be concluded that this activity can help improve cognitive function in the elderly through coloring and picture guessing group activity therapy.Keyword : Coloring, Seniors, Guessing pictures, Group activity therapy